Women’s Involvement Pattern In Grain Management Activities In Deoghar District Of Jharkhand - Rohan Prasad Gupta,; Kalyan Ghadei,; Sushree Purabi Panigrahi, (Indian Journal of Extension Education, 2024)
Post-harvest losses in India posed a significant challenge, resulting in food wastage, reduced income for farmers, and increased pressure on resources. In the context of agriculture and food security, women played a crucial role in post-harvest operations, performing tasks such as cleaning, sorting, drying, storage, processing, and marketing of agricultural products. The was study conducted in the year 2023 with a sample of120 farm women in the Deoghar district of Jharkhand, Mohanpur and Madhupur blocks were randomly selected through a lottery method out of the ten blocks. The study aimed to recognize the gender roles related to post-harvest activities in rural areas.The findings indicated that women participated in various post-harvest activities. This included the procurement of seeds (16.7%), seed treatment processes (36.7%), sowing of seeds (67.5%), drying before threshing (49.2%), threshing activities (35.8%), drying of threshed grains (60.8%), decision-making regarding pre-storage treatment (66.7%), mid-storage/intermediate treatment of grains (60.8%), and the decision to construct storage structures for grains (12.5%). The level of participation by farm women in post-harvest management highlighted the involvement of women is various post harvest activities. Transferring technical knowledge to them in need of the hour.